2010
DOI: 10.1016/j.jcf.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mealtime interactions in families of a child with cystic fibrosis: A meta-analysis

Abstract: Findings suggest that future interventions should focus on the broader family context as well as behaviors specific to feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In healthy populations, parenting and behavioural interventions have been shown to effectively reduce specific behaviour problems including sleep,28 29 and externalising and internalising behaviours 30. Educational and behavioural interventions for caregivers and children with CF have also shown benefits in decreasing child problematic eating and increasing caloric intake and weight status 6 31. Given the prevalence and persistence of the problem behaviours in children with CF, there is an urgent need to assess and offer such interventions to families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy populations, parenting and behavioural interventions have been shown to effectively reduce specific behaviour problems including sleep,28 29 and externalising and internalising behaviours 30. Educational and behavioural interventions for caregivers and children with CF have also shown benefits in decreasing child problematic eating and increasing caloric intake and weight status 6 31. Given the prevalence and persistence of the problem behaviours in children with CF, there is an urgent need to assess and offer such interventions to families.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in the relationships between behaviour problems, clinical management and child health outcomes in children with chronic illness, including CF 6 7. Common behavioural problems in children with CF include eating/mealtime behaviours and treatment adherence difficulties, particularly with regular airway clearance 814…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CF also lose energy by not taking advantage of meal and snack times. Some studies imply the constant focus on caloric intake make meal and snack times stressful, which actually results in decreased intake 32 . It has been observed that parents of children with CF describe meal times as a battleground and diet has been cited as one of the least adhered to pieces of CF treatment, particularly for young children 33 , 34 .…”
Section: Energy Lossesmentioning
confidence: 99%
“…Nonetheless, these diseases have a considerable impact on the quality of life of not only patients but also their main caregivers, who can perceive a very deleterious impact on their social, professional and family life (Michalík, 2014; Tejada-Ortigosa et al, 2019). As is the case with most childhood chronic conditions, rare diseases impact the whole family, especially with respect to normal family routines that serve an important scaffolding function for the well-being of children (Emiliani et al, 2010; Hammons and Fiese, 2010; Migliorini et al, 2011, 2016; Potì et al, 2018) as well as with respect to increases in the family’s financial burden (Dogba et al, 2013). For these reasons, the need to adopt a family centered approach to children’s chronic conditions has been repeatedly emphasized (American Academy of Pediatrics [AAP], 2003; Migliorini and Rania, 2016).…”
Section: Introductionmentioning
confidence: 99%